2010
DOI: 10.1007/s11739-010-0465-7
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with mortality in patients with exacerbation of chronic obstructive pulmonary disease hospitalized in General Medicine departments

Abstract: We aim to improve knowledge on risk factors that relate to mortality in subjects with exacerbation of chronic obstructive pulmonary disease (COPD) who are hospitalized in General Medicine departments. In a cross-sectional multicenter study, by means of a logistic regression analysis, we assessed the possible association of death during hospitalization with the following groups of variables of participating patients: sociodemographic features, treatment received prior to admission and during hospitalization, CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
3

Year Published

2011
2011
2015
2015

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 34 publications
1
8
0
3
Order By: Relevance
“…The role of the comorbidity must be carefully considered when analyzing factors related with mortality. 33 Clinical audits are a good method for benchmarking healthcare organizations. However, they sometimes yield little information on essential interventions to improve the care process.…”
Section: Discussionmentioning
confidence: 99%
“…The role of the comorbidity must be carefully considered when analyzing factors related with mortality. 33 Clinical audits are a good method for benchmarking healthcare organizations. However, they sometimes yield little information on essential interventions to improve the care process.…”
Section: Discussionmentioning
confidence: 99%
“…COPD exacerbations with a chest X-ray consistent with pneumonia are associated with worse outcomes, including inpatient mortality, 90 day mortality, and frequent readmissions 14,16,37,38 . Nantsupawat and coworkers demonstrated that a chest X-ray with pulmonary infiltrates was a risk factor for COPD early readmission 14 .…”
Section: Discussionmentioning
confidence: 99%
“…La mortalidad global observada durante el ingreso fue del 4% (16 pacientes) y se relacionó con el FEV 1 (media de 35,6 [10,2] frente a 43,6 [12,5] %; p < 0,005; intervalo de confianza del 95% [IC 95%] 0,88-0,97), aunque no con la edad (media de 73,6 [8,9] añ os frente a 77,1 [6,1] añ os; p = 0,09), el sexo (mujeres 12,5% [IC 95% 3,5-36,0] frente a un 11,3% [IC 95% 8,1-14,4]; p = 0,90) ni el nú mero de ingresos previos (6,3 [4,6] frente a 4,5 [3,9]; p = 0,07). Al alta, los pacientes ancianos fueron citados para seguir controles a asistencia primaria de forma predominante (49,5%; p < 0,001), mientras que los pacientes má s jó venes lo eran a la consulta especializada (Medicina Interna un 36,2% y Neumología un 34,5%).…”
Section: Ingreso Actualunclassified
“…EA-EPOC: exacerbació n aguda de la enfermedad pulmonar obstructiva cró nica; PCR: proteína C reactiva. (29,4) 87 (29,9) 30 (28,1) 0,770 Arritmia 108 (27,1) 72 (24,7) 36 (33,6) 0,010 Enfermedad coronaria 68 (17,1) 51 (17,5) 17 (15,9) 0,700 Arteriopatía perifé rica 50 (12,6) 32 (11) 18 (16,8) 0,120 Enfermedad cerebrovascular 38 (9,5) 24 (8,2) 14 (13,1) 0,140 Osteoporosis 37 (9,3) 26 (8,9) 11 (10,3) 0,680 Alcoholismo 56 (14,1) 50 (17,2) 6 (5,6) 0,003 Tromboembolia 13 (3,3) 12 (4,1) 1 (0,9) 0,110 Demencia 15 (3,8) 10 (3,4) 5 (4,7) 0,570 Edemas 132 (33,2) 96 (33) 36 (33,6) 0,900 Insuficiencia cardiaca 107 (26,9) 75 (25,8) 32 (29,…”
Section: Tratamientounclassified
See 1 more Smart Citation